Smart Farming for Sustainable Agriculture: A Case Study through Korean Public TVET - Wee, Youngeun; Kang, Youngah; Kim, Woocheol (Journal of Technical Education and Training, 2024)
This study aims to present implications for sustainable education and training of the agricultural workforce. It introduces the case of a smart farm learning factory as an educational facility at Korea Polytechnics. Learning factory refers to the practical experience gained using the knowledge acquired in engineering education to solve problems in the actual work field. For this study, we analyzed the smart farm case of Hongseong Campus of Korea Polytechnics, a government-funded vocational education institution in Korea. The research questions are as follows. First, what is the purpose of establishing a smart farm education and training facility? Secondly, what is the performance of the facility? Thirdly, what are the implications of the Korean smart farm for sustainable TEVT? As a result of analyzing the case, the purpose of establishing the facility was to improve the practical capabilities of convergence technologies used in machinery, automation, industrial facilities, and electrical departments. Additionally, the performance has been found to serve as the foundation for project-based learning subjects that incorporate convergence education, and companies have been able to reduce training costs and contribute to sales profits by using this facility to train employees. Finally, the implication of sustainable TVET through smart farm cases is that it has provided a way to enhance the effectiveness of teaching and learning guidance at agricultural sites, create educational resources that can utilize advanced agricultural technologies for sustainable development, and actively cooperate and collaborate with educational institutions, governments, and local companies.